1996
DOI: 10.1089/oli.1.1996.6.281
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyguanine Motifs in a 12-mer Phosphorothioate Oligodeoxynucleotide Augment Binding to the v3 Loop of HIV-1 gpl20 and Potency of HIV-1 Inhibition Independently of G-Tetrad Formation

Abstract: Phosphorothioate oligodeoxynucleotides belong to a class of polyanions that bind to the third variable domain (v3) of HIV-1 gp120 and inhibit infectivity of a wide variety of HIV-1 isolates. This potent v3 binding of phosphorothioate oligodeoxynucleotides, which is relatively independent of the nucleotide sequence of the oligodeoxynucleotides, decreases with chain length (below 18-mers) and is low for 8-mers. However, recent studies have observed a nucleotide sequence-dependent augmentation of phosphorothioate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Presumably, addition bases of the longer S-ODNs offer more potential for non-specific contacts in the yield stronger intramolecular secondary structure, thereby reducing the likelihood of binding the telomerase target. It is known that the phosphorothioate oligonucleotides blocked the proliferation HIV-1 in infected cells in a nonsequence specific manner [43], probably the inhibition of reverse transcriptase [44,45] and/or the viral entry process [46,47]. Our previous study of the anti-HIV activities of antisense oligonucleotides indicated that a phosphorothioate oligonucleotide targeted to the HIV-1 gag gene was inhibitory, and the sense and the random sequence oligomers were also able to protect against HIV-1 induced CPE, but their anti-HIV-1 activities were weaker than that of the antisense phosphorothioate oligonucleotide (S-ODN-gag-AUG) [48].…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, addition bases of the longer S-ODNs offer more potential for non-specific contacts in the yield stronger intramolecular secondary structure, thereby reducing the likelihood of binding the telomerase target. It is known that the phosphorothioate oligonucleotides blocked the proliferation HIV-1 in infected cells in a nonsequence specific manner [43], probably the inhibition of reverse transcriptase [44,45] and/or the viral entry process [46,47]. Our previous study of the anti-HIV activities of antisense oligonucleotides indicated that a phosphorothioate oligonucleotide targeted to the HIV-1 gag gene was inhibitory, and the sense and the random sequence oligomers were also able to protect against HIV-1 induced CPE, but their anti-HIV-1 activities were weaker than that of the antisense phosphorothioate oligonucleotide (S-ODN-gag-AUG) [48].…”
Section: Resultsmentioning
confidence: 99%
“…However, other mechanisms have also been found including the inhibition of virus integrase activity and of interaction of envelope glycoprotein gp120 with its receptor CD4 (Stein et al, 1991(Stein et al, , 1993Ojwang et al, 1995;Wyatt et al, 1994;Buckheit et al, 1994). For example, oligonucleotides with phosphorothioate linkages, a cytidine homopolymer (28-mer), S-dC28 (Stein et al, 1991(Stein et al, , 1993 and a guanine-rich oligonucleotide (8-mer), ISIS5320 (Wyatt etal., 1994;Lederman et al, 1996), were found to inhibit HIV-1 replication by interaction with CD4 and/or the V3loop of gp120. Moreover, guanine-rich oligonucleotides with only phosphodiester linkages were also found to exhibit anti-HIV-1 activity by interference…”
Section: Introductionmentioning
confidence: 99%
“…However, phosphorothioate oligonucleotides hybridize more weakly with the complementary nucleic acids than unmodified oligonucleotides and are eventually degraded, primarily from the 3Ј end. Antisense phosphorothioate oligonucleotides have also been shown to block the proliferation of HIV-1 in acutely infected cells in a non-sequence-specific manner (24), probably by inhibition of RT (4,25) and/or the viral entry process (21,36). On the other hand, Majumdar et al have shown that the homocytidine phosphorothioate oligonucleotide SdC28 is a potent inhibitor of HIV-1 RT with respect to template primer binding (23).…”
mentioning
confidence: 99%